Recent advances on catalysts for photocatalytic selective hydrogenation of nitrobenzene to aniline - Guo, Jiawen; Liu, Huimin; Li, Yuqiao; Li, Dezheng; He, Dehua (Frontiers in Chemistry, 2023)
Selective hydrogenation of nitrobenzene (SHN) is an important approach to synthesize aniline, an essential intermediate with extremely high research significance and value in the fields of textiles, pharmaceuticals and dyes. SHN reaction requires high temperature and high hydrogen pressure via the conventional thermal-driven catalytic process. On the contrary, photocatalysis provides an avenue to achieve high nitrobenzene conversion and high selectivity towards aniline at room temperature and low hydrogen pressure, which is in line with the sustainable development strategies. Designing efficient photocatalysts is a crucial step in SHN. Up to now, several photocatalysts have been explored for photocatalytic SHN, such as TiO2, CdS, Cu/graphene and Eosin Y. In this review, we divide the photocatalysts into three categories based on the characteristics of the light harvesting units, including semiconductors, plasmonic metal-based catalysts and dyes. The recent progress of the three categories of photocatalysts is summarized, the challenges and opportunities are pointed out and the future development prospects are described. It aims to give a clear picture to the catalysis community and stimulate more efforts in this research area.